2017
DOI: 10.1007/s00429-017-1457-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased gyrification and aberrant adult neurogenesis of the dentate gyrus in adult rats

Abstract: A remarkable example of maladaptive plasticity is the development of epilepsy after a brain insult or injury to a normal animal or human. A structure that is considered central to the development of this type of epilepsy is the dentate gyrus (DG), because it is normally a relatively inhibited structure and its quiescence is thought to reduce hippocampal seizure activity. This characteristic of the DG is also considered to be important for normal hippocampal-dependent cognitive functions. It has been suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 101 publications
(124 reference statements)
3
2
0
1
Order By: Relevance
“…It has been shown that lesions in the entorhinal cortex may induce hippocampal neurogenesis, thus emphasizing the importance of the connectivity between these two regions. Interestingly, hypergyrification of the dentate gyrus has been shown to be associated with neurogenesis in this region in a rat model of epilepsy . Further supporting our view, an overexpression of marker proteins of neurogenesis has been found postmortem in the hippocampus of AD patients, and this expression seemed to positively correlate with disease severity, suggesting that the creation of new neurons in these patients outpaces that observed in healthy conditions.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It has been shown that lesions in the entorhinal cortex may induce hippocampal neurogenesis, thus emphasizing the importance of the connectivity between these two regions. Interestingly, hypergyrification of the dentate gyrus has been shown to be associated with neurogenesis in this region in a rat model of epilepsy . Further supporting our view, an overexpression of marker proteins of neurogenesis has been found postmortem in the hippocampus of AD patients, and this expression seemed to positively correlate with disease severity, suggesting that the creation of new neurons in these patients outpaces that observed in healthy conditions.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, hypergyrification of the dentate gyrus has been shown to be associated with neurogenesis in this region in a rat model of epilepsy. 33 Further supporting our view, an overexpression of marker proteins of neurogenesis has been found postmortem in the hippocampus of AD patients, and this expression seemed to positively correlate with disease severity, 34 suggesting that the creation of new neurons in these patients outpaces that observed in healthy conditions. However, this is a subject of current debate, as a recent article reported decreased neurogenesis in AD.…”
Section: Discussionsupporting
confidence: 68%
“…In line with our video-ECoG findings, we observed upregulation of neuropeptide Y in dentate gyrus mossy fibers, alterations in granule cell layer morphology and extracellular matrix deposition in the dentate gyrus, as well as increased hippocampal gliosis in a majority of mutant animals from both lines (Figure 3 -figure supplement 1). Such findings are consistent with the presence of spontaneous seizures and altered excitability within the hippocampal circuit (Houser, 1990;Marksteiner et al, 1990;Stringer, 1996;Magagna-Poveda et al, 2017). While the site of seizure onset may differ between species, with a more prevalent role of neocortex in human compared to mouse, these results confirm that Hcn1 G380D/+ and Hcn1 M142I/+ mice are an overall appropriate model for human HCN1associated DEE, and that the two mutations are causal to the epilepsy phenotype.…”
Section: Hcn1 G380d/+ and Hcn1 M142i/+ Mice Show Spontaneous Convulsive Seizuressupporting
confidence: 79%
“…It is also in agreement with another non-spatial study reporting that approximately 10% of the cells recorded with in vivo electrophysiology in the dorsal subiculum present novelty-detecting signals in an object recognition memory task (Chang and Huerta, 2012 ). A lesion of the subiculum did however not dramatically affect performance on this task in an independent study (Potvin et al, 2010 ). In addition, indirect evidence of a contribution of the subiculum to non-spatial memory has also emerged from spatial studies, for example memory deficits in a T-maze spatial alternation task caused by a dorsal subiculum lesion were found to be the clearest in the dark, suggesting a reliance of the subiculum on non-spatial (idiothetic) cues (Potvin et al, 2007 ).…”
Section: Discussionmentioning
confidence: 86%